2006
DOI: 10.1038/sj.ki.5000377
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for microalbuminuria in a referred cohort of type II diabetic patients: A global perspective

Abstract: We described the characteristics in a referred cohort of type II diabetic patients in the Developing Education on Microalbuminuria for Awareness of renal and cardiovascular risk in Diabetes study evaluating the global prevalence and determinants of microalbuminuria (MA). A cross-sectional study evaluating 32,208 type II diabetic patients without known albuminuria from 33 countries was performed. Overall, 8057 patients were excluded, either because of prior known proteinuria or non-diabetic nephropathy (3670), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
292
8
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(345 citation statements)
references
References 36 publications
34
292
8
11
Order By: Relevance
“…In Japan, type 2 diabetic nephropathy is the main cause of chronic kidney disease (1,13). Furthermore, nephropathy accounts for a greater propor- tion of deaths in Japanese patients with type 2 diabetes than in their Caucasian counterparts (11)(12)(13)(14)(15). In the present post-hoc analysis of the INNOVATION study, we investigated whether or not treatment with telmisartan elicits beneficial effects on the progression of microalbuminuria in Japanese normotensive patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, type 2 diabetic nephropathy is the main cause of chronic kidney disease (1,13). Furthermore, nephropathy accounts for a greater propor- tion of deaths in Japanese patients with type 2 diabetes than in their Caucasian counterparts (11)(12)(13)(14)(15). In the present post-hoc analysis of the INNOVATION study, we investigated whether or not treatment with telmisartan elicits beneficial effects on the progression of microalbuminuria in Japanese normotensive patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, no comprehensive largescale study has investigated whether or not angiotensin blockade prevents the progression of albuminuria in normotensive Japanese patients with type 2 diabetes. This investigation should be particularly important because it has been revealed that Japanese diabetic patients are much more susceptible than Caucasians to end-stage renal disease (11)(12)(13)(14)(15). We recently reported on the Incipient to Overt: Angiotensin II Blocker, Telmisartan, Investigation on Type 2 Diabetic Nephropathy (INNOVATION) study to examine the effect of telmisartan, an ARB, on the progression of microalbuminuria in Japanese patients with type 2 diabetes (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A global study has reported that the overall prevalence of albuminuria in T2D to be about 50% [3]. Asian and Hispanic patients have the highest prevalence of albuminuria (55%), while Caucasians have the lowest (40.6%) [3], indicating possible ethnic differences. The pathogenesis of DN is multifactorial, and thought to come about as a result of environmental and genetic factors [4].…”
Section: Introductionmentioning
confidence: 99%
“…The current global epidemic of diabetes is expected to lead to a later increased global burden of vascular complications of diabetes [1]. Vascular complications develop progressively after 5-40 years of diabetes, although they may appear earlier in type 2 diabetes associated with a preceding period of undiagnosed diabetes and impaired glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%